Multi-channel V-doped CoP hollow nanofibers as high-performance hydrogen evolution reaction electrocatalysts. Issue 16 (16th April 2020) - Zhu, Ruolin; Chen, Fangfang; Wang, Jiayu; Song, Yuyan; Cheng, Jianlin; Mao, Mao; Ma, Huijun; Lu, Jinjun; Cheng, Yongliang
Abstract : The synergistic modulation of a multi-channel hollow structure and V doping can obviously enhance the HER performance of CoP. Abstract : Rational design and construction of high-efficiency and low-cost non-noble metal-based electrocatalysts for the hydrogen evolution reaction (HER) is critical for future renewable energy systems. Herein, a multi-channel V-doped CoP (MC-V-CoP) hollow nanofiber is fabricated via electrospinning and a subsequent oxidation/phosphorization process. The formation of a multi-channel hollow structure and V doping can enlarge the exposure of active sites, facilitate the electron transfer and tune the electronic structure of the active sites, resulting in the enhancement of the HER performance. As a result, the MC-V-CoP hollow nanofiber exhibits excellent HER activity with a low overpotential of 65 and 189 mV at 10 and 300 mA cm −2 in alkaline medium, respectively. This is superior to the commercial 20 wt% Pt/C catalyst at a high current density (212 mV at 300 mA cm −2 ), manifesting its outstanding performance toward the HER at a high current density. In addition, the MC-V-CoP hollow nanofiber also exhibits outstanding HER activity in neutral medium. The proposed strategy for fabricating multi-channel hollow nanofibers can also be used to prepare other transition metal phosphides for advanced electrochemical applications.